PENGEMBANGAN DETEKTOR SINAR-X BERBASIS FOTOTRANSISTOR DEVELOPMENT OF PHOTOTRANSISTOR BASED X-RAY DETECTOR - , Ramacos Fardela, Prof. Drs. Kusminarto ([Yogyakarta] : Universitas Gadjah Mada, 2014)
X-ray interaction with matter can produce phenomenon of fluorescence that emits visible light. This phenomenon was exploited to design an x-ray detector based on phototransistor by attaching a screen ZnS(Ag) on the surface of the phototransistor which is arranged in a Darlington circuit. Detection of active region of detector was done by collimating of x-rays beam from the x-ray generator tube Philips 2000 watts, 60 kV type PW 2215/20 NR 780 026 and measure the detector output voltage (Vout) at one millimeter change in x-ray beam position horizontally and vertically. Testing the detector response to changes in the intensity of x-rays was done by varying the current by 5 10, 15, 20, 25, 30, 35 and 40 mA in the x-ray panel. The experimental results showed that the Darlington circuit can be applied to design the detector of x-ray based on phototransistor. The active region of the detector was illuminated by x-rays obtained by (3,5Â±0,5) mm horizontally and (3,3Â±0,5) mm vertically. The results show that there is a linear relationship between the change in the intensity of x-ray detectors with voltage output phototransistor when was closed with fluorescence materials ZnS(Ag), the linearity coefficient was R 2 =0.99. Sensitivity of detector was obtained to be 4,0 Ã 10 -2 mV per cpm.